The elements of teaching - Banner, James M., Jr., 1935-; Cannon, Harold C., 1930- (New Haven : Yale University Press, 1997)
What are the characteristics of a great teacher? What qualities of mind and spirit are necessary to help others acquire the knowledge through which they can understand and live a good life? In this book, James Banner and Harold Cannon draw on many years of experience to set forth the intellectual, moral, and emotional capacities that they believe the best teachers must possess. Their book is an inspiring guide to current and future schoolteachers and to college and.
University professors - indeed to everyone who teaches anything to anyone else. Arguing that teaching is an art, Banner and Cannon help teachers understand its components. They analyze the specific qualities of successful teachers and the ways in which these qualities promote learning and understanding. Throughout, they illustrate their discussion with sharply etched portraits of fictional teachers who exemplify - or fail to exemplify - a particular quality. Neither a.
How-to book nor a consideration of the philosophy, methods, or activities of teaching, this book, more precisely, assesses what it takes to teach. It encourages teachers to consider how they might strengthen their own level of professional performance.
Learning 7 -- Authority 21 -- Ethics 35 -- Order 51 -- Imagination 67 -- Compassion 81 -- Patience 95 -- Character 107 -- Pleasure 121 -- Afterword 133.
Print version record.
JSTOR
Keywords: Teaching; Teacher effectiveness; Education; Teaching; Education; Pédagogie.; Enseignement; Enseignants -- Efficacité.; teaching; educating; EDUCATION -- Teaching Methods & Materials -- General; EDUCATION -- General; Education; Teacher effectiveness; Teaching; Lesgeven